Tantangan Implementasi Kebijakan Kepemilikan Hunian Orang Asing Pasca Undang-Undang Cipta Kerja - Debora Pasaribu; Shinta Pangesti; Elisabeth Ryanthie Maya Puteri (Media of Law and Sharia, 2024)
This research focuses on the regulation of residential ownership by foreigners after the Job Creation Law and the challenges of implementing the policy. The Researcher used statutory and conceptual approaches with secondary data in the form of legal primary, secondary, and non-legal materials, obtained through a literature study. The research found that the regulation of residential ownership by foreigners after the Job Creation Law can be seen in the Job Creation Law 2023, PP 18/2021, Permen ATR/KBPN 18/2021, and Kepmen ATR/KPBN 1241/SK-HK.02/IX/2022. Foreigners who possess immigration documents can own a house or residence, either in the form of a landed house or an apartment unit on a certain land. There are specific restrictions regarding land plots’ size, amount of land plots, land rights types, and the minimum price foreigners may own. However, in implementing existing policies, the Indonesian government must act swiftly to overcome several challenges such as double standards in calculating NPP for apartment units, violations of principles and several articles of UUPA, and the absence of a supervisory institution for foreign residential ownership. Collaboration with relevant ministries, organizations, notaries, and land deed officials is necessary so that the legal corridor established by the government can be jointly maintained and enforced.